Application of juniper (Juniperus communis) essential oil nanoemulsions to control spoilage and pathogenic bacteria in fish - Çolak, Hakan; Durmuş, Mustafa; Küley, Esmeray; Köşker, Ali Rıza; Sakarya, Yetkin; Esatbeyoglu, Tuba; Özogul, Fatih (Frontiers in Microbiology, 2026)
This study evaluated the antimicrobial activity of pure juniper essential oil and its nanoemulsion formulations (2, 4, and 6%) against five foodborne and fish spoilage bacterial species, including Staphylococcus aureus, Salmonella Paratyphi A, Vibrio vulnificus, Photobacterium damselae and Proteus mirabilis. The GC–MS profile of pure juniper essential oil (EO) revealed thirty components, including α-pinene, which accounted for 90.05% of the total volatiles. The antimicrobial activity was studied by measuring the inhibition zone diameters by the agar well diffusion method and determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values by micro dilution method. A clear dose–response relationship was observed in nanoemulsion formulations; as EO concentration increased, inhibition zones enhanced and MIC/MBC values decreased. S. aureus showed inhibition even at 2%JNEO (~15 mm), reaching a maximum of 22.1 mm at 6%JNEO. Among Gram-negative pathogens, Vibrio vulnificus showed the highest susceptibility, particularly to pure juniper essential oil, as reflected by low MIC and MBC values. P. damselae and S. paratyphi A exhibited intermediate susceptibility (MIC 1.56–12.5 mg/mL; MBC 12.5–25 mg/mL), while P. mirabilis showed high resistance (MIC 12.5 mg/mL; MBC > 100 mg/mL) and only limited inhibition. Among the tested bacteria, Staphylococcus aureus and Vibrio vulnificus showed the highest susceptibility, with inhibition zones and MIC/MBC values decreasing in a concentration-dependent manner. This antimicrobial activity may be associated with the high α-pinene content of juniper essential oil. These results highlight the potential of juniper essential oil nanoemulsions as effective natural preservatives to control fish spoilage and foodborne bacteria in the seafood industry.